The law of one price in global natural gas markets: A threshold cointegration analysis - Sebastian Nick; Benjamin Tischler (Institute of Energy Economics at the University of Cologne (EWI), 2014)
The US and UK markets for natural gas are connected by arbitrage activity in the form of shifting trade volumes of liquefied natural gas (LNG). We empirically investigate the degree of integration between the US and the UK gas markets by using a threshold cointegration approach that is in accordance with the law of one price and explicitly accounts for transaction costs. Our empirical results reveal a high degree of market integration for the period 2000-2008. Although US and UK gas prices seemed to have decoupled between 2009 and 2012, we still find a certain degree of integration pointing towards significant regional price arbitrage. However, high threshold estimates in the latter period indicate impediments to arbitrage that are by far surpassing the LNG transport costs difference between the US and UK gas market.
Keywords: Q40; Q41; G14; C51; 330; natural gas market; liquified natural gas; law of one price; arbitrage; nonlinear models; threshold error correction